2011
DOI: 10.1097/jnr.0b013e318228cd5d
|View full text |Cite
|
Sign up to set email alerts
|

The Skill Mix Model

Abstract: : This study revealed that nurses working in skill mix model environments need more authority to delegate and educate NAs and to supervise and integrate nursing care. Study results may serve as a reference for hospital nursing practice in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Additional increases in RN satisfaction upon UAP implementation included statistically significant increases in teamwork among coworkers, appropriate delegation, sense of accomplishment in their work, enjoyment coming to work, satisfaction with the workload, and satisfaction with the job 22 . McGillis Hall 19 found a statistically significant positive relationship between job satisfaction and employment on units with a regulated and UAP mix, whereas 2 studies found improved, but not significant increase in RN job satisfaction upon UAP implementation 17,18 . Contrastingly, Dzikowicz et al 16 found that RNs significantly preferred to work on the all-RN staffed unit, reporting it to be more professionally satisfying with improved time management.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Additional increases in RN satisfaction upon UAP implementation included statistically significant increases in teamwork among coworkers, appropriate delegation, sense of accomplishment in their work, enjoyment coming to work, satisfaction with the workload, and satisfaction with the job 22 . McGillis Hall 19 found a statistically significant positive relationship between job satisfaction and employment on units with a regulated and UAP mix, whereas 2 studies found improved, but not significant increase in RN job satisfaction upon UAP implementation 17,18 . Contrastingly, Dzikowicz et al 16 found that RNs significantly preferred to work on the all-RN staffed unit, reporting it to be more professionally satisfying with improved time management.…”
Section: Resultsmentioning
confidence: 97%
“…Seven of 10 articles that met the inclusion criteria were from English-speaking countries (Table 2). Locations of study included Canada (n = 4), 15,19-21 the United States (n = 3), 14,16,22 and Taiwan (n = 3) 17,18,23 . Dates of publication ranged from 1999 to 2023.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations